(untitled) (Movimenta (ISSN 1984-4298), 2021)
To verify the effect of intensive specific trunk control training protocol on the emergence of sitting with hand support in a full-term infant. A 5-month-old male, born at term, participated in an intensive specific trunk control training protocol for three consecutive days, each session totaling 45 minutes. The Brazilian version of Affordances in the Home Environment for Motor Development - Infant Scale (AHEMD-IS) questionnaire was used to characterize the affordances. The pre-training and post-training evaluations had the motor performance analyzed by Infant Motor Profile (IMP) and Alberta Infant Motor Scale (AIMS), for the segmental level of the trunk the Segmental Assessment of Trunk Control (SATCo). A positive effect of the intensive specific trunk control training protocol was observed in the domains of performance, variation, and total score of the IMP; of the seated, supine and orthostatic postures of the AIMS; and the reactive test of the trunk control by SATCo. The results indicate that the intensive specific trunk control training protocol may present a positive effect in variation and motor performance, and on the reactive trunk control of infants after three days of training, demonstrating the potential for early intervention practices.